LEARNERS' SELF-ACTUALIZATION AND INCLUSIVE EDUCATION PRACTICES IN MADRASAH - El Rizaq, Agung; Ambarwati, Amiroh; Abdullah, A. Fatikhul Amin; Sukartiningsih, Sri (JPI (Jurnal Pendidikan Inklusi), 2024)
The availability of equal access to education for all parties is the main mission of Islamic education, including for students with special need (SWSN). Madrasah as one of Islamic education has reforms to be better in quality, accreditation, and user access. This study aims to explore the practice of inclusive education (IE) in Madrasah. This study used an exploratory descriptive quantitative research approach. The data gained by online surveys (to educators and both regular and SWSN students’ parents) on Java Island. This study uses Maslow's hierarchy of needs theory to analyze each founding. This study shows that the first hierarchy of Maslow's theory, namely physiological needs, is realized in the form of fulfilling facilities in inclusive practices in madrasahs. The next is the second hierarchy of security of the body needed by students with needs, including fulfilling the need for supporting tools for their learning process. Employment can be realized by having teachers who make it easier for students with needs to learn. The resources needed are in the form of learning resources that are in accordance with the characteristics of each limitation of students with needs. Furthermore, the third hierarchy is the need for love and a sense of belonging in the form of a sense of belonging to education together. Furthermore, the form of esteem need is in the form of a shared desire to make the inclusive program a success. Finally, self-actualization is realized by achieving the potential of each student. The findings of this study also confirm that collaboration between educators and parents are environment support that develop s meaningful learning quality and lead students to reach self-actualization successfully.